2020
DOI: 10.1038/s41598-020-72764-3
|View full text |Cite
|
Sign up to set email alerts
|

Sequence polymorphism of the waxy gene in waxy maize accessions and characterization of a new waxy allele

Abstract: Waxy maize has many excellent characteristics in terms of its nutritional and economic value. In recent decades, the waxy maize germplasm has increased dramatically as a result of different selection methods. We collected 200 waxy maize inbred accessions from different origins to study their genetic diversity and phylogenetic relationships, and to identify new waxy mutations. A simple sequence repeat (SSR) analysis revealed wide genetic diversity among the 200 waxy maize accessions. The maize accessions were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Since the cloning of the Wx gene in the 1980s, transgenic lines with various ACs have been established using antisense RNA, homologous recombination, and overexpression, and the effects of different ACs on starch physicochemical properties have been clarified ( Shimada et al., 1993 ; Terada et al., 2000 , 2002 ; Itoh et al., 2003 ; Liu et al., 2015a ). In recent years, diverse Wx alleles have been cloned in rice, maize, wheat, and barley ( Asare et al., 2012 ; Guzmán and Alvarez, 2016 ; Luo et al., 2020 ). Cloning of numerous null wx alleles in maize has enabled the convenient breeding of waxy maize with a unique chewing texture.…”
Section: Genetic Improvement Of Cereal Starch Qualitymentioning
confidence: 99%
“…Since the cloning of the Wx gene in the 1980s, transgenic lines with various ACs have been established using antisense RNA, homologous recombination, and overexpression, and the effects of different ACs on starch physicochemical properties have been clarified ( Shimada et al., 1993 ; Terada et al., 2000 , 2002 ; Itoh et al., 2003 ; Liu et al., 2015a ). In recent years, diverse Wx alleles have been cloned in rice, maize, wheat, and barley ( Asare et al., 2012 ; Guzmán and Alvarez, 2016 ; Luo et al., 2020 ). Cloning of numerous null wx alleles in maize has enabled the convenient breeding of waxy maize with a unique chewing texture.…”
Section: Genetic Improvement Of Cereal Starch Qualitymentioning
confidence: 99%
“…in waxy rice, resulting in the loss of GBSS function, which in turn causes the glutinous trait (Inukai et al, 2000;Wanchana et al, 2003;Teng et al, 2012). In parallel with waxy or glutinous rice, genetic identification and association mapping of the waxy gene in maize have been characterized in the recent decades (Huang et al, 2010;Hossain et al, 2019;Luo et al, 2020;Kim H. R. et al, 2021). The waxy gene of wild maize was located in chromosome 9 and comprised of 14 exons by 3.93 kb long (Luo et al, 2020), and has a higher genetic variation level than rice, representing most of the identified waxy mutations by insertions and deletions, such as wx-m9, wx-m5, wx-B3, wx-m1, and wx-B4 (Huang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with waxy or glutinous rice, genetic identification and association mapping of the waxy gene in maize have been characterized in the recent decades (Huang et al, 2010;Hossain et al, 2019;Luo et al, 2020;Kim H. R. et al, 2021). The waxy gene of wild maize was located in chromosome 9 and comprised of 14 exons by 3.93 kb long (Luo et al, 2020), and has a higher genetic variation level than rice, representing most of the identified waxy mutations by insertions and deletions, such as wx-m9, wx-m5, wx-B3, wx-m1, and wx-B4 (Huang et al, 2010). Up to the recent updates, despite the presence of several mutant waxy alleles (>50) in maize (Huang et al, 2010), a low number (≥ 10) of waxy alleles (Wx a , Wx b , Wx in , Wx mp , Wx mq , Wx op/hp , Wx Iv , Wx mw , Wx Ia , and wx) have collectively been discovered in rice genome (Cai et al, 1998;Larkin and Park, 2003;Wanchana et al, 2003;Liu et al, 2009;Yang et al, 2013;Zhang et al, 2021;Zhou et al, 2021), and summarized for the identification of their specific polymorphic sites carrying different functional properties (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the differences in specific expression patterns and protein locations of GBSSII and GBSSI [3], the two genes encoding these proteins share high sequence similarity with almost 66% identical deduced amino acid sequences in wheat [3] and about 70% homology at the nucleotide sequence level in rice [4]. However, several different functional alleles or haplotypes [12][13][14] have been identified in the waxy gene (GBSSI) region and are associated with amylose content in rice and many other crops, such as maize [15], wheat [16], barley [17], and cassava [18,19], but research on the functional properties of GBSSII gene in crops is limited, particularly in rice. A recent study reported novel GBSSII haplotypes in rice through genome-wide identification and genetic variation analyses [20], but additional evolutionary analyses on this gene have not been performed.…”
Section: Introductionmentioning
confidence: 99%